WHY IS IT NECESSARY TO STUDY THE PEDAGOGICAL ROUTINE? - Alevtina S. Robotova (Moscow Polytechnic University, 2016)
The article is devoted to the problem of daily routine, which today has become a subject of active research in Humanities and Social Sciences. The author believes that it is also interesting for pedagogical science and gives her opinion on the need of its pedagogical study.